2003
DOI: 10.1002/pola.11013
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of new segmented polyurethanes with side‐chain, liquid‐crystalline chain extenders

Abstract: Liquid‐crystalline, segmented polyurethanes with methoxy–biphenyl mesogens pendant on the chain extender were synthesized by the conventional prepolymer technique and esterification reaction. Two, side‐chain, liquid‐crystalline (SCLC) polyurethanes with mesogens having spacers of six and eight methylene units were prepared. The structures of the mesogenic units and SCLC polyurethanes were confirmed by Fourier transform infrared spectroscopy and 1H NMR. Polymer properties were also examined by solubility tests,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The decomposition of all the polymers was completed at 600 C and no further weight loss was observed. The thermal stability decreases with increasing methylene chain length in the polymers [27]:…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…The decomposition of all the polymers was completed at 600 C and no further weight loss was observed. The thermal stability decreases with increasing methylene chain length in the polymers [27]:…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…The decomposition was completed at 600°C, and no further weight loss was observed. The TGA data suggested that thermal stability and char yield of the polymers decreases with increasing number of methylene units in the following order [42–44]:…”
Section: Resultsmentioning
confidence: 99%
“…35 M n and polydispersity determined by gel permeation chromatography are 90,400, and 1.68, respectively. The reaction is given in Scheme 1.…”
Section: Synthesis Of the Segmented Pudmentioning
confidence: 99%
“…Since characterization of PUD has been published elsewhere, 35 this part will only concern about the characterization of MWNT-PUD. The molecular composition of the resulting MWNT-polyurethane nanohybrids was confirmed by FTIR and WAXD measurements.…”
Section: Synthesis and Characterization Of Mwnt-pudmentioning
confidence: 99%